IMPLEMENTATION OF THE SIMPLE ADDITIVE WEIGHTING (SAW) METHOD IN THE SELECTION OF THE BEST EMPLOYEESAT PT. SAWITA INTER PERKASA - Yeremia Margaretta Aritonang; Zulfi Azhar; Mardalius Mardalius (Jurnal Teknik Informatika (Jutif), 2022)
PT.SawitaInter Perkasa is a private companyengaged in oilpalmand operating in 2007. The company has obstacles in selecting the best employees in the process ofentering data written and the result soft hehead of section meeting. The purposeo fthis study wasto assist the admin in selecting the best employees using the Simple Additive Weighting Method. The research method used in this study is a qualitative research method, namely by finding information about the company and the problems that exist in the company and collecting data after that enter into research using employee data processing. The result of this research is a program that providesan alternative way of processing and inputting the best employee selection data. This study concluded that the application of the simpl eadditive weighting method can help carry out the process of selecting the best employees effectively and also helps the company to accelerate the processof selecting the best employee sat PT. Sawita Inter Perkasa.